2006
DOI: 10.1111/j.1399-3054.2006.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines are involved in the gynogenesis process in onion

Abstract: Haploidization in onion (Allium cepa L.) using immature flower buds simulates zygotic embryogenesis with no fecundation. In order to know the involvement of polyamines (PAs) in this process, we determined the concentration of endogenous PAs in flower buds and experimented the addition of various combinations of PA molecules in the medium. At the inoculation stage, high levels of free and conjugated spermidine and low putrescine þ hydroxyputrescine/spermidine þ spermine ratio characterized the highest responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…This is a similar result to that of the exogenous application of 5-7.5 mM Spd in the TN-1 rice variety, which led to a low level of Put and a high number of plantlets per callus piece Rajam 1995, 1996). Polyamines play a key role in plant growth and development, especially in plant morphogenesis, as small trigger molecules for endogenous hormone regulation and amino acid supporters (Walden et al 1997;Bais and Ravishankar 2002;Geoffriau et al 2006). Plantlet regeneration from calli derived from anther or pollen culture using polyamine application has been investigated in plants such as citrus (2 mM Spd; 763 embryos; Chiancone et al 2006), Guizotia abyssinica (200 μM Spd; 57 embryos; Hema and Murthy 2008), and onion (0.1 mM Spd and 2 mM Put; six embryos in Valcatorce INTA cultivar and ten embryos in Torrentina cultivar; Martínez et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This is a similar result to that of the exogenous application of 5-7.5 mM Spd in the TN-1 rice variety, which led to a low level of Put and a high number of plantlets per callus piece Rajam 1995, 1996). Polyamines play a key role in plant growth and development, especially in plant morphogenesis, as small trigger molecules for endogenous hormone regulation and amino acid supporters (Walden et al 1997;Bais and Ravishankar 2002;Geoffriau et al 2006). Plantlet regeneration from calli derived from anther or pollen culture using polyamine application has been investigated in plants such as citrus (2 mM Spd; 763 embryos; Chiancone et al 2006), Guizotia abyssinica (200 μM Spd; 57 embryos; Hema and Murthy 2008), and onion (0.1 mM Spd and 2 mM Put; six embryos in Valcatorce INTA cultivar and ten embryos in Torrentina cultivar; Martínez et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…5b), corresponding, respectively, to fertilization and formation of the zygotic embryo. Geoffriau et al (2006) showed the involvement of PAs in the gynogenesis of Allium cepa, where the Put/Spd-Spm Table 1 Amino acids content (lg g -1 FW) in zygotic embryos during seed development in A. sellowiana 3.6 ± 0.9 5.9 ± 0.9…”
Section: Polyamines (Pas)mentioning
confidence: 99%
“…There are relatively fewer reports on the participation of polyamines in gametic embryogenesis (Forodi et al, 2009). An improvement in the efficiency of gynogenesis in onion has been achieved through the exogenous application of polyamines (Martinez et al, 2000;Geoffriau et al, 2006). The role of polyamines in androgenesis has been investigated by Tiainen (1992) in potatoes, Dewi et al (2004) and Dewi and Purwoko (2008) in rice, Kumar et al (2004) in cucumbers, Hema et al (2008) in niger (Guizotia abisinica L.), and Chiancone et al (2006) in clementines.…”
mentioning
confidence: 99%